Tingkat Keberdayaan Petani dalam Penerapan Low External Input Sustainable Agriculture (LEISA) pada Budidaya Ubi Jalar di Kecamatan Cilawu Kabupaten Garut - Qintamy, Riestania Anindhita; Harniati, Harniati; Kusnadi, Dedy (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2020)
The dependence of farmers on the use of high external inputs causes farmers to be independent and ignore environmental aspects. The lack of independence of farmers makes farmers powerless in utilizing local resources. The application of LEISA enables farmers to minimize the use of external inputs and be able to utilize local resources. The purpose of this study is to determine the level of empowerment of farmers, determine the factors that influence and formulate appropriate strategies to increase empowerment. Data collection was conducted from March to July 2020. Data analysis used descriptive analysis and multiple linear regression analysis. The conclusion of the study shows that the strategy of increasing empowerment can be done by expanding land, increasing farmer institutional support, increasing the availability of information sources.